Bridging the Academic–Vocational Gap: A Needs Analysis for Developing a Project-Based English Module in an Agribusiness Context - Elva Bonita Arbie; Nonny Basalama; Sartin T Miolo; Muziatun Mukadji; Hasanuddin Fatsah; Rasuna Talib (Universitas Islam Negeri Palopo, 2026)
The demand for English proficiency in vocational education requires instructional materials that align with students’ professional contexts. Although English for Specific Purposes (ESP) and Project-Based Learning (PjBL) have been widely explored in vocational education, studies integrating ESP needs analysis, Agribusiness-specific content, Project-Based Learning, and the Merdeka Curriculum remain limited. This study aims to identify the target needs and learning needs of Agribusiness students at SMKN 1 Paguyaman as a basis for developing an ESP module integrated with Project-Based Learning. This research represents the Analysis phase of the ADDIE model and employed a descriptive needs analysis design. Data were collected through document analysis of the Phase F English Learning Outcomes and questionnaires administered to one English teacher, three Agribusiness productive teachers, and 18 eleventh-grade Agribusiness students. The data were analyzed using qualitative descriptive analysis involving data reduction, data display, and conclusion drawing. The findings revealed a gap between curriculum expectations and classroom practices, particularly regarding limited technical vocabulary and the lack of contextualized instructional materials. Specifically, 88% of students reported difficulty understanding English vocabulary, while 93% expressed a need for agriculture-related procedural text materials. Procedure and descriptive texts were identified as the most relevant text types, whereas Project-Based Learning and interactive audio features were considered effective in supporting student engagement and comprehension. The novelty of this study lies in integrating ESP needs analysis, Agribusiness-specific content, Project-Based Learning, and the Merdeka Curriculum as a foundation for developing contextualized instructional materials. The study concludes that a contextualized ESP module is essential to bridge the gap between content knowledge and students’ language competence.